2017
DOI: 10.1007/s11307-017-1093-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Magneto-Endosymbionts as MRI Cell Labeling and Tracking Agents

Abstract: Purpose Magneto-endosymbionts (MEs) show promise as living magnetic resonance imaging (MRI) contrast agents for in vivo cell tracking. Here we characterize the biomedical imaging properties of ME contrast agents, in vitro and in vivo. Procedures By adapting and engineering magnetotactic bacteria to the intracellular niche, we are creating magneto-endosymbionts (MEs) that offer advantages relative to passive iron-based contrast agents (superparamagnetic iron oxides, SPIOs) for cell tracking. This work present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…AMB-1 coordinates over 100 genes to synthesize membrane enclosed magnetic nanoparticles, (magnetosomes), which are highly effective MRI contrast agents24. In metastatic breast cancer cells, ME-labeled cells show strong contrast with as few at 100 ME-labeled cells, demonstrating high sensitivity for detection25. More importantly, the MEs do not appear to persist long-term in macrophages, eliminating any confounding MRI signal of cell viability.…”
mentioning
confidence: 99%
“…AMB-1 coordinates over 100 genes to synthesize membrane enclosed magnetic nanoparticles, (magnetosomes), which are highly effective MRI contrast agents24. In metastatic breast cancer cells, ME-labeled cells show strong contrast with as few at 100 ME-labeled cells, demonstrating high sensitivity for detection25. More importantly, the MEs do not appear to persist long-term in macrophages, eliminating any confounding MRI signal of cell viability.…”
mentioning
confidence: 99%
“…In the literature, r 1 and r 2 of the iron oxide particles (in particular, Molday ION) have been reported at different field strengths. For example, the vendor's website (http://www.biopal.com/pdf-downloads/data-sheets/data-sheet-CL-30Q02-2.pdf, accessed 2019/05/24) provides r 1 = 36 [s -1 mM -1 ] and r 2 = 71 [s -1 mM -1 ] at 0.47 T. Brewer et al [15] reported r 2 = 178 [s -1 mM -1 ] at 7T for particles with comparable magnetic core with different functionalization. Given that r 1 decreases and r 2 increases with the main magnetic fields [16], our results of r 1 = 6.1 [s -1 mM -1 ] and r 2 = 142 [s -1 mM -1 ] at 3T are compatible with the literature values.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, non-toxic forms of iron compounds such as ferumoxytol, magneto-endosymbionts, bicycle[6.1.0]nonyne-modified glycol chitosan nanoparticles (BCN-CNPs) have been tested successfully [26][27][28][29]. Among them, ferumoxytol has been found as an FDA approved agent for clinical applications [30].…”
Section: Iron Particlesmentioning
confidence: 99%
“…Because, low contrast is the main disadvantage of reporter genes for tracking of stem cells, scientists have tried to improve MRI signals using novel or dual reporter gene imaging. Development of novel reporter genes such as T cell immunoglobulin and mucin domain containing protein 2, adenoviral vector encoding ferritin heavy chain and magneto-endosymbionts are some example that have been produced in recent years [61][62][63]. In a study by Guo et al studied tracing of MSCs in rabbit using two reporter genes including ferritin heavy subunit and transferrin receptor.…”
Section: Reporter Genesmentioning
confidence: 99%